Progressionen 1 : Foto - Film - Dias - Zeichnung. (Köln : [s.n.], 1974)
Adamski, Hans Peter ; Bartz, E.H. ; Becker, Krimhild ; De Boek, R. ; Breloh, Heinz ; Charlier, Jacques ; Eins, Stefan ; Gerz, Jochen ; Gette, Paul-Armand ; Gravier, Nikole ; Hendriks, Martin ; Hubert, Pierre ; Jordan, Marga ; Kuppel, Edmund ; Leisgen, Barbara & Michael ; Lennep, Jacques ; Lizene, Jacques ; Lundberg, Bill ; Marroquin, Roul ; Maul, Reiner ; Muntadas, Antoni ; Neur, Christoph Mc ; Nyst, Jacques-Louis ; Perneczky, Géza ; Pick, Peter ; Prangenberg, Eberhard ; Reiners, Lothar ; Schäffer, Matthias ; Schweizer, Helmut ; Schwind-Foundation ; Stavenhagen, Andrey ; Stembera, Petr. ; Stumm, Reiner
Progressionen 1 : Foto - Film - Dias - Zeichnung, Kupferdruck Werkstatt, Moltkestrasse 27, Köln 5, 29.6. - 21.7.74. Verantwortlich H.P. Adamski, M. Jordan, M. Schäffer, Moltkestrasse 27, Köln 5
boek